Effect of gallic acid as a final irrigant on push-out bond strength of an epoxy resin sealer to root canal dentin - Sarath Kumar; Kavitha Sanjeev; Nagarathinam Sundaramoorthy; Sekar Mahalaxmi (Shahrekord University of Medical Sciences, 2023)
Introduction: Ethylenediaminetetraacetic acid (EDTA), a widely used chelating agent, compromises the bond strength of resin-based sealers when used as a final irrigating solution. Hence, the push-out bond strength of AH Plus, a resin-based sealer, was analyzed when gallic acid, "a chelator" was used as a last irrigating solution. Methods: Forty human single-rooted teeth were accessed and randomly assigned into 4 groups (n = 10): EA (17% EDTA), MA (7% maleic acid), GA (10% gallic acid), and SA (saline). After irrigation, the root canals were coated with AH Plus sealer and obturated using gutta-percha. The root canals were sectioned horizontally into coronal, middle, and apical thirds for evaluating the push-out bond strength. A universal testing machine with a compressive loading of 1 mm/min was employed to test the samples. Results: An increased push-out bond strength was noted with GA in coronal one-third compared to EA and SA but not significant compared to MA (P > 0.05). Similar observations were seen in the middle one-third; however, it was statistically significant compared to all other groups (P < 0.05). Also, the difference between the groups in the apical one-third was not significant. SA showed the lowest push-out bond strength than experimental groups, which was significant in all three sections (P < 0.05). Conclusion: The final rinse of 10% gallic acid increased the push-out bond strength of AH Plus to the root dentin in all thirds of the root canal. Hence, gallic acid 10% might be an effective alternative solution in place of synthetic chelators.